2005
DOI: 10.1111/j.1095-8339.2005.00419.x
|View full text |Cite
|
Sign up to set email alerts
|

A morphometric study of three closely related taxa in the European Isoetes velata complex

Abstract: Isoetes velata A. Braun is an amphibious plant with Mediterranean and Ibero‐Atlantic distribution, showing marked morphological variability. Within the same geographical area, closely related restricted‐range taxa are also present, including I. velata ssp. asturicense (restricted to mountainous areas of the north‐west Iberian Peninsula) and I. boryana (restricted to the southern French Atlantic coast). These related taxa have unclear taxonomy and are both threatened. We performed a morphometric study of specim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…1). The microspore of I. boryana shown in Romero & Real (2005) is different, however, from the microspore of I. longissima (the two are shown side by side in the same article). Prada & Rolleri (2005) found another character separating I. boryana from I. velata/longissima, i.e., the lack of intercellular pectic protuberances (IPP) in the cells of the translacunar diaphragms of the microphylls.…”
Section: Isoetes Boryanamentioning
confidence: 94%
See 3 more Smart Citations
“…1). The microspore of I. boryana shown in Romero & Real (2005) is different, however, from the microspore of I. longissima (the two are shown side by side in the same article). Prada & Rolleri (2005) found another character separating I. boryana from I. velata/longissima, i.e., the lack of intercellular pectic protuberances (IPP) in the cells of the translacunar diaphragms of the microphylls.…”
Section: Isoetes Boryanamentioning
confidence: 94%
“…Some authors described the microspores of I. boryana as either smooth (Hy, 1894;Berthet & Lecocq, 1977;Rolleri & Prada, 2007) or very minutely scabrid (Berthet & Lecoq, 1977;Jermy & Akeroyd, 1993) or sub-papillose (Rolleri & Prada, 2007). Prelli (2002) and Romero & Real (2005), however, reported echinate miscropores, similar to those of I. longissima. Our investigations found only non-echinate microspores (Fig.…”
Section: Isoetes Boryanamentioning
confidence: 99%
See 2 more Smart Citations
“…Based on morphometric differences together with other distinguishing characteristics as habitat, Romero & Real (2005) have suggested that I. asturicense (Laínz) Laínz should be considered as separate species of I. velata. In this work, megaspore characteristics and habitat attributes in Isoetes populations from the western Iberian Peninsula, where both I. velata susbp.…”
Section: Introductionmentioning
confidence: 99%